2015
DOI: 10.1007/s11192-015-1769-1
|View full text |Cite
|
Sign up to set email alerts
|

Publication trends and co-citation mapping of translation studies between 2000 and 2015

Abstract: Literature regarding translation studies has increased rapidly in recent decades, yet there have been few empirical studies to investigate the research context of translation studies at the global level. A bibliometric analysis was carried out in this research to probe the current status and the research themes of translation studies papers published between 2000 and 2015 in all journals indexed by the Web of Science database. Bibliometric methods and knowledge visualization technologies were employed to thoro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 31 publications
0
28
0
2
Order By: Relevance
“…In this study, we identified publications that are indexed in the Thomson Reuters Web of Science Core Collection (WoSCC) database, namely, the Science Citation Index Expanded, the Social Sciences Citation Index, and the Emerging Sources Citation Index. As WoSCC comprised most high-quality literature, and being updated continuously and dynamically, it has been identified as being most appropriate for the bibliometric analysis in this study [ 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…In this study, we identified publications that are indexed in the Thomson Reuters Web of Science Core Collection (WoSCC) database, namely, the Science Citation Index Expanded, the Social Sciences Citation Index, and the Emerging Sources Citation Index. As WoSCC comprised most high-quality literature, and being updated continuously and dynamically, it has been identified as being most appropriate for the bibliometric analysis in this study [ 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…This type of analysis allows for the understanding of the field of study's structure by observing the related study areas according to the number of citations shared in the reference journals [164,165]. In the formation of this network, 345 sources were considered, which had at least 20 citations.…”
Section: Scientific Cited Sources Co-citation Networkmentioning
confidence: 99%
“…The analysis allows us to observe the study field's structure according to the reference journals that have allowed its construction [75,89]. In this network's configuration, the threshold of at least 20 co-citations established, which has allowed us to consider 49 journals that meet the requirement.…”
Section: Scientific Journal Co-citation Networkmentioning
confidence: 99%